Precipitation strengthening and reversed yield stress asymmetry in Mg alloys containing rare-earth elements: A quantitative study. (1st February 2017) - Hidalgo-Manrique, P.; Robson, J.D.; Pérez-Prado, M.T.
Abstract: The effect of prismatic plates on the mechanical behaviour at low and high temperature of a Mg-1 wt.% Mn- 1 wt%Nd alloy was determined. For this purpose, a weakly textured extruded bar, exhibiting similar values for the critical resolved shear stresses of the various deformation systems, was annealed at 275 °C for different time periods. During these thermal treatments the grain size and texture remained invariant, but different precipitate distributions, characterised by transmission electron microscopy (TEM), were generated. The as-extruded and the annealed material were tested under tension and compression at room temperature (RT) and 250 °C along the extrusion direction. Precipitation was observed to harden the alloy at RT and to induce a reversed yield stress (YS) asymmetry, the compressive YS being higher than the tensile YS. At 250 °C, the alloy is anomalously resistant under compressive conditions, exhibiting an enhanced reversed YS asymmetry. In order to assess the strengthening effect of particles on the individual major Mg deformation systems, appropriate versions of the Orowan equation were developed. The correlation of the predicted results with the experimental data revealed that reversed YS asymmetry at RT is attributable to a strong promotion of prismatic slip over twinning. Finally, experimental observations by TEM suggested that reversed YS asymmetry at high temperature arises from a different interaction of pyramidal dislocations with particles and solutes in tension and compression. Graphical abstract: Image 1